2017
DOI: 10.1186/s12882-017-0762-8
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis and risk of hypertension: a meta-analysis of observational studies

Abstract: BackgroundObservational studies have demonstrated an association between nephrolithiasis and hypertension. The aim of this meta-analysis was to summarize all available evidence.MethodsPubMed, EMBASE, the Cochrane Central Register of Controlled Trials databases, and the reference lists of relevant articles were searched to identify observational studies that reported study-specific risk estimates comparing the risk of hypertension in patients with nephrolithiasis. We used a random-effect model to pool the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…Similar observations were made by Sarica et al, showing that children with high body mass and urolithiasis tended to have higher systolic blood pressure (34) . An association between urolithiasis and arterial hypertension was also demonstrated by Shang et al in a meta-analysis of observational studies (35) .…”
Section: Discussionsupporting
confidence: 55%
“…Similar observations were made by Sarica et al, showing that children with high body mass and urolithiasis tended to have higher systolic blood pressure (34) . An association between urolithiasis and arterial hypertension was also demonstrated by Shang et al in a meta-analysis of observational studies (35) .…”
Section: Discussionsupporting
confidence: 55%
“…In the study of Kalani et al [26] 29.7% of patients with nephrolithiasis had hypertension, which is consistent with our results. Also, Shang et al [27] showed that the risk of nephrolithiasis was directly associated with hypertension incidence. In addition, it has been shown that patients with hypertension as a related factor of the metabolic syndrome are more susceptible to kidney stones [5].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with published literature, the SFs in the current study had higher BMI and incidence of HTN, HLD, DM and smoking compared NSFs of equivalent age and gender. These comorbidities are independently linked to atherosclerosis and nephrolithiasis, making them possible contributors of biomineral deposition (1)(2)(3)(4)(5)(6)(7)15,16). Increased age, HLD, male gender, and history of nephrolithiasis were significantly and independently associated with increased ectopic mineralization burden among all patients.…”
Section: Discussionmentioning
confidence: 99%